ANALYSIS OF IMPLEMENTATION SAFETY AND HEALTH OCCUPATIONAL IN WORKSHOPS AND LABORATORIES OF POLYTECHNIC (CASE STUDY: POLYTECHNIC X) - Kartika Hapsari Sutantiningrum; Kusumo Drajad Sutjahjo; Safri Safri (LPPM, 2023)
Learning activities at Polytechnics are mostly carried out with practice to be able to create graduates who meet the qualifications according to industry needs. Practical activities, especially in engineering study programs so that the safety system in carrying out practices needs to be managed so as to minimize the potential risk of accidents. In this study, researchers wanted to know the level of application of SMK3 in workshops and laboratories at polytechnic colleges. The research method used is a quantitative method by providing an assessment of 166 criteria contained in the K3 audit PP No. 50 of 2012, data collection is carried out by filling out questionnaires, interviews and collecting OHS records to respondents then assessing the achievement of implementation (less, good or satisfactory). . The results of the study indicate that the average implementation of SMK3 in the workshop and laboratory at Polytechnic X is 23%, which means the level of application assessment is less. The highest score in the skill and capability development element is 53%, most of the laboratory assistants and technicians have been included in basic K3 and first aid training, this shows that the leadership is aware of the importance of occupational safety and health in their environment but also needs to be given training that is in accordance with the competencies to support her job. The lowest value is found in elements of document control, data collection and use and inspection of SMK3 at 0%, this happens because there are no standard rules to regulate how the SMK3 reporting system in workshops and laboratories.